2023
DOI: 10.1039/d3mh00745f
|View full text |Cite
|
Sign up to set email alerts
|

Alternating chiral and achiral spacers for constructing two-dimensional chiral hybrid perovskites toward circular-polarization-sensitive photodetection

Shihai You,
Panpan Yu,
Tingting Zhu
et al.

Abstract: Using a half substitution strategy, a pair of 2D chiral hybrid perovskites with alternating spacers, (R/S-phenylpropylamine)(pentylamine)PbBr4, are derived from an achiral (pentylamine)2PbBr4 for circularly polarized light detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…[9][10][11][12] Moreover, benefiting from the excellent semiconductor properties brought by the inorganic framework, including high optical absorption, defect tolerance, and long carrier lifetime, 2DHPs have also sparked great research enthusiasm in the field of photoelectric detection. [13][14][15][16][17][18] Therefore, 2DHPs are considered an ideal platform for integrating dielectric switching and photo-responsivity features, thereby promoting the development of multifunctional materials. For example, Sun et al reported a series of 2DHPs that synchronously exhibited excellent photosensitivity and giant dielectric anomalies, showcasing their significant application value.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Moreover, benefiting from the excellent semiconductor properties brought by the inorganic framework, including high optical absorption, defect tolerance, and long carrier lifetime, 2DHPs have also sparked great research enthusiasm in the field of photoelectric detection. [13][14][15][16][17][18] Therefore, 2DHPs are considered an ideal platform for integrating dielectric switching and photo-responsivity features, thereby promoting the development of multifunctional materials. For example, Sun et al reported a series of 2DHPs that synchronously exhibited excellent photosensitivity and giant dielectric anomalies, showcasing their significant application value.…”
Section: Introductionmentioning
confidence: 99%
“…One is to use intrinsically chiral materials. These materials could be chiral molecules, chiral polymers, or crystals with structures of chiral space groups, e.g., chiral perovskites. The other is to build the chiral layer from intrinsically achiral structured materials by constructing the chiral shape, pattern, morphology, or assembly in the feature size from nanometer to micrometer scales. The latter breaks the material limitations that principally any materials, organic or inorganic, conductor, semiconductor, or even insulator can be effective candidates. It brings about opportunities of converting achiral photodetective materials into chiral counterparts by various methods such as CPL irradiation, , templating, , grazing angle deposition, laser direct writing, electron beam lithography, , chiral molecule induced nanocrystal synthesis, , or film growth. Among the chiral candidates, inorganic semiconducting materials may have a tunable band structure, higher carrier mobility, and good stability, making them suitable for building high-performance CPL photodetectors. , …”
Section: Introductionmentioning
confidence: 99%